The Effect of Muslim Women' Clothing Style to Their Communication to Men - Sarmiah, Lindia; Rahman, Rini (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2023)
This study aims to analyze the effect of a Muslim woman wearing Muslimah dress on the way she communicates with men. This study used quantitative methods with a survey and correlation approach, data sources were taken using a questionnaire with a Likert scale of five from forty-seven students who were selected using the simple random sampling in one of the State Universities in Indonesia. All data were then analyzed using descriptive and correlation techniques using SPSS Version 22 software. Overall the results of the analysis show that Muslim women who are fully clothed and comply with religious guidelines have an effect on the way they communicate with a man, such as not looking at the man fully. the other man, avoiding direct communication with men who are not relatives, speaking softly, lowering his voice. Furthermore, the results of the correlation analysis show that there is an influence on how to dress a Muslim woman on the way she communicates with other people, especially men. The results of the study concluded that the way a Muslim woman dresses can shape her attitude in communicating as well as protect herself from committing disgraceful acts.